Comparative Analysis of Multiple Neurodegenerative Diseases Based on Advanced Epigenetic Aging Brain - Shi, Feitong; He, Yudan; Chen, Yao; Yin, Xinman; Sha, Xianzheng; Wang, Yin (Frontiers in Genetics, 2021)
Background: The Neurodegenerative Diseases (NDs) are age-dependent, including Alzheimer’s disease (AD), Parkinson’s disease (PD), progressive supranuclear palsy (PSP), frontotemporal dementia (FTD) and so on. There have been numerous of studies shown that accelerated aging is closely related (even the driver of) ND, thus by promoting the cellular homeostasis imbalances. However, the mechanisms of how different ND types are related/triggered by advanced aging are still unclear. Therefore, it is urgent to explore potential markers/mechanisms of different ND types based on aging acceleration at system level. Method: The AD, PD, PSP, FTD as well as aging markers were identified by supervised machine learning methods. The aging acceleration differential networks were constructed on the basis of the aging score. Both the enrichment analysis and sensitivity analysis were carried out to investigate both common and specific mechanisms among different ND types in the context of aging acceleration. Results: The extracellular fluid, cellular metabolisms, and the inflammatory response were identified as the common driven factors of cellular homeostasis imbalances during the accelerated aging process. In addition, Ca ion imbalance, abnormal protein depositions, DNA damage, and cytoplasmic DNA in macrophages were alsorevealed to be special mechanisms which further promote AD, PD, PSP and FTD, respectively. Conclusion: In sum, the accelerated epigenetic aging mechanisms of different ND types were integrated and compared through our computational pipeline.